A posthumanist re-reading of teacher agency in times of curriculum reform - Appadoo-Ramsamy, W. (South African Journal of Higher Education, 2023)
Teacher agency in times of curriculum reform has often been researched and studied from a humanist perspective that focuses on human experiences and narratives. While this way of conducting research has contributed to a better understanding of curriculum design and implementation, it is nevertheless important to move away from a human-centred approach and to consider intra-actions between teachers and their material conditions as they inhabit multiple macro-policy and micro-institutional spaces across temporal dimensions. In this article, emphasis is laid on teacher agency as a hybrid collective between teachers and others (policy documents, formal and informal infrastructures, technology, textbooks). Teacher agency is consequently re-thought as a fluid process of entangled and diffracted possibilities that is not predetermined, but as a result of intra-actions, it is one that is always in “becoming”.